(untitled) (Journal of Advanced Research in Social Sciences, 2020)
As one of the major phenomena in the contemporary global context, consumerism has been shaping lifestyles in different aspects. Signifying the demand for the consumption of the properties that are produced and accessed quickly, consumerism has not only shaped the tendencies for the consumption of products, but it has also had impact on the approach to interpersonal relations in cultural, social and individual areas. In contemporary British fiction, Kamila Shamsie focuses on the disillusionment of the immigrants with their hopes for a civilised life due to their consideration as “outsiders” and she views this as an embodiment of the consumption of their dreams for the future in Home Fire (2017). Zadie Smith reflects the consumerist approach to the relations among family members in On Beauty (2005) with reference to Howard Belsey’s affair with Victoria as a signification of the quest for his new self and his failed efforts for the reconciliation with his family. However, in The Nothing (2017), Kureishi reveals that consumerism also leads to temporary sexual relations among the people. Focusing on Zee’s affair with Eddie instead of her husband, Waldo because of his old age and infertility, Eddie’s sexual relations with Patricia and Sarah, Kureishi’s The Nothing invites reading in relation to its focus on the short-term sexual relations among the people as an embodiment of the consumerist approach to interpersonal relations and an inevitable quest for a new personal identity within the dynamism of the contemporary world.